2009
DOI: 10.1542/peds.2008-1647
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Respiratory Therapist-Driven Protocol for Neonatal Ventilation: Impact on the Premature Population

Abstract: In this study, we were able to demonstrate for the first time a significant improvement on the weaning time and duration of mechanical ventilation with the implementation of a ventilation protocol driven by a registered respiratory therapist in the premature population. Based on our experience, other institutions can customize ventilation protocols to their local practice. However, a prospective, randomized, controlled study should be planned to evaluate long-term outcomes such as BPD and neurodevelopment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 25 publications
4
40
1
2
Order By: Relevance
“…Por outro lado, a extubação tardia, como discutido anteriormente, está associada à piora da lesão pulmonar e ao aumento dos marcadores inflamatórios. O aumento da atividade inflamatória, por sua vez, tem sido associado a uma maior incidência de HIC e à reabertura do canal arterial 22,26,27 .…”
Section: Resultados Secundáriosunclassified
See 1 more Smart Citation
“…Por outro lado, a extubação tardia, como discutido anteriormente, está associada à piora da lesão pulmonar e ao aumento dos marcadores inflamatórios. O aumento da atividade inflamatória, por sua vez, tem sido associado a uma maior incidência de HIC e à reabertura do canal arterial 22,26,27 .…”
Section: Resultados Secundáriosunclassified
“…Em nosso estudo, observamos uma diferença marcante, embora não significativa, na idade pós-natal à extubação (sucesso = 33 horas versus falha = 115 horas; p = 0,07). Recentemente demonstramos, numa população com PN e IG semelhantes, que a simples introdução de um protocolo de VM, com o estabelecimento de critérios para extubação e reintubação baseados em evidências, foi capaz de reduzir significativamente a incidência de falha na extubação em recém-nascidos desconectados mais precocemente (5 dias versus 1,2 dia) 22 .…”
Section: Desmame Da Vmunclassified
“…Szymankiewicz et al 13 assessed the pulmonary mechanics of VLBW newborns evidence-based criteria for extubation and reintubation, was able to provide a significant reduction in the incidence of extubation failure in newborns who were extubated earlier (5 days vs. 1.2 day). 22 The use of methylxanthines also reduces time on MV, mainly in newborns with BW < 1,000 g who are extubated…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several studies have failed to show a significant difference in subject outcomes between protocol and non-protocol RT. 2,3 However, Hermeto et al 4 found that protocol RT in the neonatal ICU significantly reduced weaning time in mechanically ventilated neonates compared with non-protocol RT. Similarly, protocol RT was found to reduce the duration of mechanical ventilation in adult subjects.…”
Section: Introductionmentioning
confidence: 99%